Evaluasi Dana Desa dan Dampaknya Terhadap Pembangunan di Desa Rasau Jaya Umum Kecamatan Rasau Jaya Kabupaten Kubu Raya - B1011141035, Ade Irwinda Sabania (Jurnal Pembangunan dan Pemerataan, 2018)
Evaluasi Dana Desa Dan Dampaknya Terhadap Pembangunan Di Desa Rasau Jaya Umum Kecamatan Rasau Jaya Kabupaten Kubu Raya  Ade Irwinda SabaniaProgram Studi Ekonomi Pembangunan, Universitas Tanjungpura ABSTRACT               The purpose of this study was to analyze the distribution and use of Village Funds, find out and analyze the level of knowledge and community participation in the Village Fund, to find out and analyze governance of Village Fund implementation from the perspective of village officials and community leaders and to know and analyze the impact of development in agriculture originating from Village Funds in Rasau Jaya Umum Village, Rasau Jaya District, Kubu Raya District. The analytical method used in this study is descriptive and evangelical using percentage analysis (%) and presented with tables. In the percentage analysis using this table discusses community knowledge and participation, governance of the implementation of the Village Fund, and the impact of the Village Fund. The results of the analysis show that the distribution and use of Village Funds in Rasau Jaya Umum Village in 2016-2017 from the point of view of village officials and community leaders has largely gone well, starting from the fields of communication, resources, attitudes, bureaucratic structures, environment and policy objectives . Then viewed from the community's point of view, the result is that most say it has not gone well, which is not in line with existing planning, implementation and evaluation. Village funds have a positive impact on development and community empowerment. Most of the development has been carried out and has contributed to the improvement of village infrastructure, of course this facilitates the activities of farmers in carrying out their economic activities. Keywords: Evaluation, Village Funds, Development Impacts